Supply Chain Risk Mitigation Analysis Using the House of Risk (HOR) and Interpretive Structural Modeling (ISM) Methods Approach - Najwa Ratna Dewanty; Dira Ernawati (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2026)
Supply chain disruptions have become increasingly complex due to uncertainty in global markets, operational inefficiencies, and external environmental factors. Effective risk mitigation strategies are therefore essential to ensure supply chain resilience and sustainability. This study aims to analyze and prioritize supply chain risk mitigation strategies using an integrated approach of House of Risk (HOR) and Interpretive Structural Modeling (ISM). The HOR method was employed to identify risk events and risk agents, evaluate their aggregate risk potential, and determine priority mitigation actions based on their effectiveness-to-difficulty ratio. Subsequently, ISM was applied to analyze the interrelationships among selected mitigation strategies and to establish a hierarchical structural model for implementation. The results indicate that several dominant risk agents significantly influence supply chain performance, including supplier delivery delays, inaccurate demand forecasting, and inadequate information sharing. The HOR analysis identified the most critical preventive actions, while the ISM results revealed the driving and dependent factors among mitigation strategies, enabling a systematic implementation sequence. The integration of HOR and ISM provides a comprehensive framework for both quantitative risk prioritization and structural strategic planning. This study contributes to supply chain risk management literature by offering a practical decision-support model for organizations seeking to enhance supply chain resilience through structured and prioritized mitigation planning.